Valores y Juventud: Una perspectiva sociológica - Viveros, Licer (Revista Chilena de Humanidades, 2016)
After commenting on fundamental sociological value functions, the author proceeds to describe different situations where the value plane either associates with social interaction, or becomes its result. In that context, juvenile attitudes which originate in values held by the young themselves, are described as tightly connected with their personal experience from the mornent of self or ego discovery. And if such values are to imply responsability as well as selective critical appreciation, sociological investigation together with a pragmatic value orientation are fundamental to this passage from youth to maturity.